The thermal expansion of single-walled carbon nanotubes at low temperatures - Dolbin, A.V. (Functional Materials, 2009)
The radial thermal expansion coefficient αr of pure and Xe-saturated bundles of singlewalled carbon nanotubes has been measured in the interval 2.2-120 K. The coefficient is positive above T = 5.5 K and negative at lower temperatures. The sample was prepared by compacting a CNT powder such that the pressure applied oriented the nanotube axes perpendicular to the axis of the cylindrical sample. The data show that individual nanotubes have a negative thermal expansion coefficient while the solid compacted material has a positive one due to expansion of the intertube volume in the bundles. Doping the nanotubes with Xe caused a sharp increase in αr in the whole temperature range used, and a peak in the dependence αr(T) in the 50-65 K interval. A subsequent decrease in the Xe concentration lowered the peak considerably but had a little effect on the thermal expansion coefficient of the sample outside the peak region. The features revealed have been explained qualitatively. В інтервалі температур 2,2-120 К виміряно коефіцієнти радіального теплового розширення αr чистих та насичених ксеноном джгутів одностінних вуглецевих нанотрубок. Значення αr є додатними вище 5,5 К та від'ємними при нижчих температурах. Досліджений зразок одержано пресуванням порошку нанотрубок, в результаті якого осі нанотрубок були орієнтовані перпендикулярно осі зразка. Одержані результати дозволяють припустити, що значення ar індивідуальних нанотрубок від'ємні, тоді як для об'ємного зразка, внаслідок вкладу джгутів нанотрубок, αr є додатним. Допування нанотрубок ксеноном спричинило різке збільшення абсолютних значень ar в усьому інтервалі температур, який досліджено, а також виникнення піка на залежності αr(T) у температурному інтервалі 50-65 К. Наступне зниження концентрації домішки ксенону спричинило істотне зменшення величини піка, однак практично не вплинуло на значення коефіцієнта теплового розширення зразка поза областю піка. Запропоновано якісне пояснення виявлених особливостей. В интервале температур 2,2-120 К измерены коэффициенты радиального теплового расширения αr чистых и насыщенных ксеноном жгутов одностенных углеродных нанотрубок. Значения αr положительны выше 5,5 К и отрицательны при более низких температурах. Исследованный образец получен прессованием порошка нанотрубок, в результате которого оси нанотрубок были ориентированы перпендикулярно оси образца. Полученные результаты позволяют предположить, что значения αr индивидуальных нанотрубок отрицательны, тогда как для объемного образца, ввиду вклада жгутов нанотрубок, ar положительны. Допирование нанотрубок ксеноном привело к резкому увеличению абсолютных значений αr во всем исследованном интервале температур, а также к возникновению пика на зависимости αr(T) в температурном интервале 50-65 К. Последующее уменьшение концентрации примеси ксенона привело к существенному снижению величины пика, однако практически не повлияло на значения коэффициента теплового расширения образца вне области пика. Предложено качественное объяснение обнаруженных особенностей.